Marx: a relação sociedade-natureza - Schian, Rodolfo Medeiros (2011)
We live in turbulent times of social and ecological crises, and many researchers believe that these are associated, and often are the responsibility of the capitalist system. This linkage of social and environmental problems was seen only in 1960, with the emergence of environmental sociology, concluding that the degradation of natural resources was linked to industrial development. However, for many researchers sociologists, this issue, experienced by the company, could not be thoroughly examined in the absence of a theory to explain the relationship between society and nature as the classics of sociology (Marx, Weber and Durkheim), worked on environmental issues so tangential in his theories. Thus, this research was conducted to understand the concept of nature of Karl Marx, if in fact the environmental issue has been addressed tangentially in his work, as this classical thinker reflected the society-nature relationship in socialist theory, and what the extent of their concepts to understand the ecological problem. Through analysis of his major works and some Marxists, we found a thought developed on the relationship between society and nature, a conception of the revolutionary nature of its time, and above all, a theory developed by means of historical materialism, which serves as a basis for analyzing contemporary ecological problems. Marx had already completed what sociologists have concluded only in 1960 that the degradation of natural resources is associated with the capitalist industrial development. Thus, we conclude that socialism and ecology are involved